Matilda di Canossa (1046-1115) la donna che mutò il corso della storia = Matilda of Canossa (1046-1115) : the woman who changed the course of history - Spike, Michèle K.; Cecchi, Alessandro 1949- (Centro Di, 2016)
Nine hundred years after her death, the first monographic exhibition dedicated to Matilda di Canossa in Florence opens at the Casa Buonarroti. Florence was particularly favored by her as the city where she lived during her youth. Casa Buonarroti also celebrates the family of Canossa with heraldic symbols of a dog (cane) and a bone (osso). The catalogue which is richly illustrated, contains a series of essays about the countess and her legacy, a chronology of the long and tumultuous life of Matilda and the catalogue of the works of art, documents and illuminated manuscripts which are shown in the exhibition. - Catalog of an exhibition held at an itinerant exhibition held at the Muscarelle Museum of Art, Williamsburg, United States, Febr. 7-Apr. 19, 2015, and at the Casa Buonarroti, Florence, Italy, June 14-Oct. 10, 2016. - First publ. in 2015 in English by Muscarelle Museum of Art, with the title Matilda of Canossa and the origins of the Renaissance, now revised and enlarged. - M. di Canossa (1046-1115), contessa. - Includes bibliographical references